2014
DOI: 10.2174/1568026614666140118223412
|View full text |Cite
|
Sign up to set email alerts
|

Recent Contributions of Elastin-Like Recombinamers to Biomedicine and Nanotechnology

Abstract: Abstract:The emergence of the new scientific field known as nanomedicine is being catalyzed by multiple improvements in nanoscience techniques and significant progress in materials science, especially as regards the testing of novel and sophisticated biomaterials. This conjuncture has furthered the development of promising instruments in terms of detection, bioanalysis, therapy, diagnostics and imaging. Some of the most innovative new biomaterials are protein-inspired biomimetic materials in which modern biote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 157 publications
0
26
0
Order By: Relevance
“…They are produced by genetic engineering techniques, [4] which ensures an absolute control over the amino acid composition and the achievement of a completely monodisperse material. [5] Furthermore, functional groups can be inserted in the repeating sequence obtaining in this way desired bioactive properties. ELRs have been shown to maintain important aspects of the natural elastin, such as the elastic behavior, the cytocompatibility, [6,7] the low thrombogenicity [8][9][10] and the inverse transition behavior [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…They are produced by genetic engineering techniques, [4] which ensures an absolute control over the amino acid composition and the achievement of a completely monodisperse material. [5] Furthermore, functional groups can be inserted in the repeating sequence obtaining in this way desired bioactive properties. ELRs have been shown to maintain important aspects of the natural elastin, such as the elastic behavior, the cytocompatibility, [6,7] the low thrombogenicity [8][9][10] and the inverse transition behavior [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…All these properties explain the increasing interest for these materials in biomedical applications. [5,[12][13][14] We have recently shown that ELRs could be chemically modified at their lysine groups to bear azide and cyclooctyne groups to enable the formation of hydrogels by a catalyst-free click chemistry reaction [15] . Click chemistry [16][17][18][19] (and concretely Huisgen 1,3-dipolar cycloadition of azides and alkynes) has proven itself to be superior to other crosslinking…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus, they can be used as soluble delivery systems when fused to therapeutic proteins in a recombinant manner, or as pharmacokinetic enhancers, either by chemical conjugation or by fusion protein expression of the drug [17]. A monomeric ELR carrier allows the pharmacokinetics and biodistribution of its drug load to be improved when compared to the free drug, thus resulting in specific delivery of the therapeutic agent [18]. Moreover, the genetic engineering of elastin-like recombinamers allows targeting peptides, such as receptor ligands or cell-penetrating domains, to be incorporated and reactive sites useful for covalent chemical conjugation of drugs to be included into the ELR sequence [19].…”
Section: Advanced Drug Delivery Devices From Elrsmentioning
confidence: 99%
“…This is the case for elastin-like recombinamers (ELRs), a type of recombinant biopolymers with a structure based on elastin, the extracellular elastic protein found in higher animals [1]. As these recombinamers are designed at the gene level, the high precision control in gene construction is transferred onwards into the final polypeptide, thus meaning that their physical and bioactive properties can be finely tuned as desired using the most appropriate amino acid composition for different biomedical and nanotechnological applications [2][3][4]. The degree of control and complexity of such recombinamers is not practically achievable using more conventional synthetic technologies.…”
Section: Introductionmentioning
confidence: 99%